Psychology of sport injury rehabilitation: a review of models and interventions - Santi, G.; Pietrantoni, L. (Journal of Human Sport & Exercise, 2013)
The aim of this review is to provide the state of the art about the psychology of sport injury rehabilitation by analyzing the most recent literature and research on this field. In the first part we provide theoretical models contextualizing the sport injury, the motivational process underlying the recovery, and the influence of social and contextual factors. In the second part we analyze the possible psychological interventions and their effect on the rehabilitation process. In conclusion we highlight some gaps in the current literature and we propose directions for future research.